Investigating Students’ Views on the Role of Generative AI in Academic Writing - Utami Rosalina; Salah Abobaker Almabruk Shahat; Naufal Fidha Sulaeman (Journal of General Education and Humanities, 2026)
The rapid integration of Generative Artificial Intelligence (GenAI) in higher education has raised pedagogical and ethical concerns regarding its role in academic writing. This study investigates students’ views on the anticipated functions, perceived benefits, and challenges of AI-assisted academic writing. A convergent parallel mixed-methods design was employed, involving 89 second-year students with prior experience using GenAI tools. Quantitative data were analyzed using descriptive statistics, and qualitative interview data were analyzed using thematic analysis. The findings indicate that most students perceive GenAI as a writing assistant (85%) and feedback provider (78%). A substantial proportion report increased writing efficiency (82%) and improved writing quality (76%) when using GenAI tools. However, concerns regarding over-dependence (45%) and potential plagiarism risks (32%) were also identified. Overall, students position GenAI as a supportive pedagogical aid that enhances drafting and revision processes while acknowledging important ethical and cognitive challenges. These findings highlight the need for structured instructional guidance and the development of AI literacy to ensure responsible and pedagogically aligned integration of GenAI in academic writing instruction.